Seguro de acidentes de trabalho e solidarismo constitucional como instrumentos de proteção social para um trabalho decente - Costa, Raíssa Maria Falcão (2018)
The present work analyzes the Work Accident Insurance - SAT, as an obligatory contribution of the employer, who comes to support the worker in case of incapacity for work, through the implementation of an accidental benefit. In this sense, according to art. 7, XXVIII, CRFB / 88, is the right of the injured worker, who can not be left out of social protection. Notwithstanding the payment of the contribution to the SAT, the employer must continue to pay attention to the protection of the working environment, so that the number of accidents and, consequently, the accidental benefits implemented are reduced. This is why it is important to analyze the issue through the principle of constitutional solidarity: firstly, in view of the very nature of SAT insurance, which imposes the need for risk contributions (solidarity), and is also a basic principle of Social Security; second, because of the decent work that, in order to be fulfilled, demands the participation of companies, the State and the entire social fabric. Thus, the payment of the SAT can not constitute an excuse to the employer for his general duty of caution in the work environment, because in an accident, the costs of this are diluted throughout society. In order to avoid such a vicious circle and in view of the fact that the social values of work must guide economic activity, there is still a need to prevent labor misfortunes, and it is up to the employer, in particular, to undertake protective measures in his or her work environment to achieve decent work. Therefore, the present research makes use of the hypothetico-deductive approach. With regard to research techniques, data collection based on documentary research is used, as well as statistical data from official databases.